2014
DOI: 10.2135/cropsci2013.07.0506
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Resistance to Sunflower Diseasesin a Global Collection of Domesticated USDA Plant Introductions

Abstract: Basal stalk rot (BSR) and head rot (HR) caused by Sclerotinia sclerotiorum (Lib.) de Bary are traditionally major diseases of sunflower (Helianthus annuus L.) in the United States, while Phomopsis stem canker (PSC) caused by Phomopsis helianthi Munt.‐Cvet. et al. has become increasingly damaging in recent years. Host resistance is the most effective approach to managing these diseases. Here we report new sources of resistance to these diseases identified in the USDA sunflower Plant Introduction (PI) collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 27 publications
5
61
1
Order By: Relevance
“…Broad‐sense heritability ( H 2 ), which estimates the proportion of phenotypic variance that is due to genetic factors, was moderately high (69%), lending further validation to our assumption that the observed variation for DI was mainly explained by the genetic makeup of the RILs. This result is consistent with our previous observations for this trait, where the genotype had much larger effect than the genotype × environment interaction (Talukder et al, 2014b). Despite significantly different environments and highly variable mean DI across environments, the Spearman's rank correlation coefficients for DI among environments were highly significant (Table 3), suggesting a general agreement of repeatability of the screening trials across different environments.…”
Section: Discussionsupporting
confidence: 93%
“…Broad‐sense heritability ( H 2 ), which estimates the proportion of phenotypic variance that is due to genetic factors, was moderately high (69%), lending further validation to our assumption that the observed variation for DI was mainly explained by the genetic makeup of the RILs. This result is consistent with our previous observations for this trait, where the genotype had much larger effect than the genotype × environment interaction (Talukder et al, 2014b). Despite significantly different environments and highly variable mean DI across environments, the Spearman's rank correlation coefficients for DI among environments were highly significant (Table 3), suggesting a general agreement of repeatability of the screening trials across different environments.…”
Section: Discussionsupporting
confidence: 93%
“…Currently, there are no cultivated sunflower inbred lines or commercial hybrids that possess an acceptable level of resistance to Sclerotinia (Hahn, 2002; Gulya, 2005; Talukder et al, 2014, 2016). In an effort to manage sunflower Sclerotinia disease, numerous wild Helianthus species were screened for their reaction to Sclerotinia head rot and stalk rot.…”
Section: Discussionmentioning
confidence: 99%
“…The latter two diseases cause serious losses of yield and seed quality during epidemic years under appropriate environmental conditions. Field evaluation of germplasm for resistance to Sclerotinia BSR and HR revealed that there was no correlation between the two, suggesting a different inheritance of resistance to Sclerotinia in sunflower (Gulya et al, 1989; Talukder et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imidazolinone herbicide tolerance testing was conducted using the field method described by Hulke and Gulya (2015), in which 20 plants were backpack sprayed with a 2× labeled rate of imazamox (Beyond herbicide, BASF). Sclerotinia head rot (HR) and Sclerotinia stalk rot (SR) evaluation of testcrosses was conducted at Carrington and Casselton, ND, respectively, in 2004 and 2005 using the method described by Hulke and Gulya (2015) and Talukder et al (2014). For HR evaluation, field‐grown plants were inoculated at bloom with lab‐produced ascospores of S. sclerotiorum isolate ‘NEB‐274’ at a concentration of 5 × 10 3 spores mL −1 in distilled water.…”
Section: Methodsmentioning
confidence: 99%